High Level Expert Group Committee on Universal Health Coverage Instituted by The Planning Commission of India Progress Report - Planning Commission (Planning Commission, 2010)
With the aim of incorporating a comprehensive plan for health within the 12th Five- Year Plan, the Planning Commission, under approval by the Prime Minister, constituted a High Level Expert Group (HLEG) on Universal Health Coverage (UHC), which has been assigned the task of reviewing the experience of India's health sector and suggesting a 10-year strategy going forward. The overall charge of the Committee is to develop a framework for Universal Health coverage, to be progressively implemented over 2010-2020. (Please refer to Appendix I for the membership and terms of reference of the HLEG)
Planning Commission
Planning Commission